Pendampingan dan Implementasi Aplikasi Bank Sampah Pada TPS-3R Banjar Bonjaka - I Made Darma Susila; Made Liandana; Dandy Pramana Hostiadi; Yohanes Priyo Atmojo; Gede Angga Pradipta; Putu Desiana WUlaning Ayu; Abdul Wahab; Muhamad Rihamzah (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
Garbage is a common problem that needs serious attention. Waste problems can have an impact on public health and environmental health. The local governments and community's form of effort in dealing with waste problems is the formation of TPS-3R by applying the concept of reduce, reuse, and recycle. Implementing the TPS-3R Institution requires proper management with the support of information technology. One of the TPS-3Rs located in the Gianyar – Bali area is TPS-3R Banjar Bonjaka which provides waste processing services for 345 households. The problem encountered during the observation was the manual recording of TPS-3R operational activities. The recording is currently only in the form of a physical book which carries the risk of errors, loss of records, and physical damage. Thus, in carrying out community service activities, it is proposed to provide assistance activities and implement the Garbage Bank application for TPS-3R managers. Community service activities aim to increase the ability to use information technology to manage TPS-3R. Thus, it can help optimize administrative governance. The activity was carried out for one day and attended by 10-15 participants. The evaluation of community service activities shows that participants have been able to input or manage data in the waste bank application. Achievement of abilities is a benchmark for the success of community service activities, with a success percentage of around 80-90%. This activity's benefit is facilitating administrative recording and management of TPS-3R activities by implementing the waste bank application.